2019
DOI: 10.33094/7.2017.2019.52.72.83
|View full text |Cite
|
Sign up to set email alerts
|

Health Expenditure and Child Health Outcome in West Africa

Abstract: The study examines the long run relationship between public health expenditure and under-five mortality rate in 15 West African countries over the period of 1991-2015 with the use of panel fully modified least square (FMOLS). The empirical analysis is made up of both aggregate and disaggregated model. Based on the findings, long run relationship between per capita health expenditure and under-five mortality rate is confirmed. Further evidence indicates that public health expenditure has a significant impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The GDP per-capita was found to be positively significant, which indicates that a 1% increase in GDP per-capita leads to about a 2.5% increase in the under-five mortality rate in Malaysia. Almost all the relevant literature reviewed in this study reported either a negative relationship [ 18 , 25 ] or no significance [ 8 , 9 , 11 , 13 ]. Except for Kulkarni [ 15 ], whereby a positive, significant relationship was revealed between GDP per-capita and infant mortality rate in an analysis among BRICS countries (Brazil, Russia, India, China, and South Africa).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The GDP per-capita was found to be positively significant, which indicates that a 1% increase in GDP per-capita leads to about a 2.5% increase in the under-five mortality rate in Malaysia. Almost all the relevant literature reviewed in this study reported either a negative relationship [ 18 , 25 ] or no significance [ 8 , 9 , 11 , 13 ]. Except for Kulkarni [ 15 ], whereby a positive, significant relationship was revealed between GDP per-capita and infant mortality rate in an analysis among BRICS countries (Brazil, Russia, India, China, and South Africa).…”
Section: Resultsmentioning
confidence: 99%
“…Based on recent studies [ 8 , 9 , 11 , 12 , 25 ], the health capital model, as in Equation (1) is respecified by including the health expenditure ( and other control variables ( ), as follows: …”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Using the fixed-effect approach, they established a positively strong association between health expenditure and life expectancy and a negative relationship between under-five mortality, neonatal mortality and infant mortality. In West Africa, Olatunde et al (2019) employed a panel fully modified least square from 1991 to 2015. Their study established a long-run relationship between health expenditure and the under-five mortality rate, and it significantly reduced infant mortality.…”
Section: Literature Reviewmentioning
confidence: 99%